Lithium ion battery composite electrolyte, battery and preparation method
Patent Information
- Application Number
- CN202611305963.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-30
AI Technical Summary
但在实际应用中,中镍三元||石墨电池常面临高压(4.35~4.5V)充电和高温(60~85℃)搁置的双重工况,仍存在亟待解决的技术痛点,严重影响电池的存储稳定性和使用寿命
(1)显著提升高温高压搁置后的容量保持率和恢复率,有效延长电池在高温工况下的使用寿命。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials, and in particular relates to a lithium-ion battery composite electrolyte, battery, and preparation method. Background Technology
[0002] High-nickel layered oxide cathode material (molecular formula LiNi) x Co y Mn 1-x-y O2 (x≥0.8) cathode materials, due to their higher specific capacity compared to traditional cathode materials such as lithium manganese oxide, lithium iron phosphate, and lithium cobalt oxide, have been widely researched and applied in academia and industry, becoming a core choice for improving the energy density of lithium-ion batteries. However, high-nickel cathode materials suffer from problems such as high risk of metal ion dissolution, poor thermal stability, and high cost, limiting their application in some safety- and cost-sensitive scenarios. Against this backdrop, medium-nickel ternary cathode materials (with the molecular formula LiNi) have emerged as a promising candidate. x Co y Mn 1-x-y O2 (x=0.65~0.75) has rapidly risen to prominence due to its balanced advantages in energy density and stability. When its charging voltage is increased to 4.4V, its energy density is basically close to that of high-nickel materials at conventional voltages, while also possessing a lower risk of metal ion dissolution and better cost control. However, in practical applications, medium-nickel ternary graphite batteries often face the dual challenges of high-voltage (4.35~4.5V) charging and high-temperature (60~85℃) storage, and there are still technical pain points that urgently need to be addressed, which seriously affect the storage stability and lifespan of the batteries.
[0003] Under high pressure and high temperature conditions, the performance degradation of medium-nickel ternary / graphite batteries mainly stems from three aspects: First, the lattice oxygen on the surface of the medium-nickel ternary cathode is easily released, leading to oxidative decomposition of the electrolyte at the cathode interface. Simultaneously, Ni²⁺… + Co³ + Firstly, ions dissolve and migrate to the graphite anode, catalyzing the reduction and decomposition of the electrolyte, thus destroying the solid electrolyte interphase (SEI) film on the anode surface. Secondly, high temperatures accelerate the hydrolysis reaction of lithium salts (such as LiPF6) in the electrolyte, generating corrosive substances such as HF, which further corrode the positive and negative electrode interphase films, leading to film rupture and regeneration, and consuming a large amount of active Li. + The electrolyte and its properties cause irreversible loss of battery capacity and a surge in internal resistance; thirdly, interfacial side reactions and electrolyte decomposition produce gases such as CO2 and olefins, leading to battery bulging and seriously affecting the storage safety and lifespan of the battery.
[0004] Furthermore, existing multi-additive electrolyte formulations often employ simple combinations of 2-3 additives (such as only film-forming additives and lithium salt additives), failing to recognize that in medium-nickel ternary / graphite batteries, cathode dissolution, interface aging, and electrolyte hydrolysis are interconnected chain reactions under high voltage and high temperature conditions. Single-dimensional additive optimization cannot achieve stability under all operating conditions. For example, adding only film-forming additives (such as VC) can improve the initial stability of the anode SEI film, but it cannot suppress the catalytic damage to the film layer caused by dissolved metal ions from the cathode; adding only lithium salt additives (such as LiPO2F2) can form a cathode CEI film, but it cannot solve the acid corrosion problem caused by electrolyte hydrolysis at high temperatures. Simultaneously, existing solvent systems often use EC:EMC binary mixed solvents, resulting in a narrow electrochemical window (≤4.3V), making it difficult to adapt to high voltage requirements above 4.4V. Moreover, the solvent ratio is not optimized for the oxygen release characteristics of medium-nickel cathodes, leading to a higher risk of electrolyte oxidation and decomposition under high voltage.
[0005] In summary, there is an urgent need to develop an electrolyte that can synergistically suppress the aforementioned multiple failure mechanisms in order to improve the cycle stability of medium-nickel ternary graphite batteries under high voltage of 4.35~4.5V and high temperature of 60~85℃. Summary of the Invention
[0006] The purpose of this invention is to overcome the above-mentioned technical problems and provide a lithium-ion battery composite electrolyte, battery, and preparation method.
[0007] The specific technical solution to achieve the above-mentioned objectives is as follows: In a first aspect, the present invention provides a lithium-ion battery composite electrolyte, the composite electrolyte comprising electrolyte A and electrolyte B; electrolyte A comprising lithium salt, ester solvent, and negative electrode film-forming additive; electrolyte B comprising lithium salt, ester solvent, positive electrode interface stabilizer, negative electrode film-forming additive, and water-removing and acid-suppressing additive; electrolyte A accounting for 50wt% to 80wt% of the total mass of the composite electrolyte, and electrolyte B accounting for 20wt% to 50wt% of the total mass of the composite electrolyte.
[0008] Furthermore, the lithium salts in electrolyte A and electrolyte B each independently include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bisfluorosulfonylimide, lithium bistrifluoromethanesulfonylimide, lithium difluorooxalate borate, lithium bisoxalate borate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium fluorosulfonate, and lithium perchlorate.
[0009] Furthermore, the lithium salts in electrolyte A and electrolyte B are both mixtures of lithium hexafluorophosphate and lithium difluorosulfonylimide, and the mass ratio of lithium hexafluorophosphate to lithium difluorosulfonylimide in electrolyte A and electrolyte B is independently 12:1 to 1:4. Based on the total mass of electrolyte A, the mass fraction of lithium salt in electrolyte A is calculated to be 10%~25%. Based on the total mass of electrolyte B, the mass fraction of lithium salt in electrolyte B is calculated to be 10%~25%.
[0010] Lithium hexafluorophosphate and lithium difluorosulfonylimide were used as lithium salts. Lithium difluorosulfonylimide has better hydrolytic and thermal stability, which can suppress HF corrosion caused by lithium salt hydrolysis at high temperature. At the same time, its anions can participate in the formation of a stable interface film rich in LiF at the positive and negative electrode interfaces, and synergistically improve the high temperature stability of the electrolyte with lithium hexafluorophosphate.
[0011] Furthermore, the ester solvents in electrolyte A and electrolyte B each independently include at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, and methyl butyrate.
[0012] Furthermore, the ester solvent of electrolyte A is a mixture of ethylene carbonate and methyl ethyl carbonate, wherein the volume ratio of ethylene carbonate to methyl ethyl carbonate is 1:4 to 4:1; the ester solvent of electrolyte B is a mixture of propylene carbonate and methyl ethyl carbonate, wherein the volume ratio of propylene carbonate to methyl ethyl carbonate is 1:9 to 1:1.
[0013] Electrolyte A uses a mixed solvent of ethylene carbonate and methyl ethyl carbonate, which balances high dielectric constant and low viscosity, which is beneficial for lithium salt dissociation and ion transport. Electrolyte B uses propylene carbonate to replace part of the ethylene carbonate. Propylene carbonate has a lower melting point and a higher boiling point. Combined with methyl ethyl carbonate, it can broaden the liquid temperature range of the electrolyte and improve high-temperature stability. At the same time, the weak solvation effect of propylene carbonate helps to reduce the dissolution rate of the interfacial film at high temperatures.
[0014] Furthermore, the volume ratio of ethylene carbonate to methyl ethyl carbonate in electrolyte A is 3:7; and the volume ratio of propylene carbonate to methyl ethyl carbonate in electrolyte B is 3:7.
[0015] Further, the negative electrode film-forming additive of electrolyte A includes at least one of vinylene carbonate, fluoroethylene carbonate, and vinyl sulfate, and the mass fraction of the negative electrode film-forming additive of electrolyte A is 0.1wt% to 5wt% of the total mass of electrolyte A; the negative electrode film-forming additive of electrolyte B includes at least one of vinylene carbonate and 1,3-propane sulpholactone (PS), and the mass fraction of the negative electrode film-forming additive of electrolyte B is 0.1wt% to 3wt% of the total mass of electrolyte B.
[0016] PS and MMDS have dual functions in electrolyte B: on the negative electrode surface, the sulfonic acid groups, which are decomposed products of the CEI membrane polymer backbone, play a role in increasing the toughness of the interfacial membrane; on the high-voltage positive electrode surface, the two can preferentially oxidize and form deposit products to repair the micropores of the CEI membrane.
[0017] Furthermore, the negative electrode film-forming additive of electrolyte A is a mixture of vinyl sulfate and fluoroethylene carbonate, or a mixture of vinyl sulfate and vinylene carbonate, or a mixture of vinyl sulfate, fluoroethylene carbonate, and vinylene carbonate. In electrolyte A, vinyl sulfate (DTD) is compounded with fluoroethylene carbonate (FEC) and / or vinylene carbonate (VC) as the negative electrode film-forming additive. DTD preferentially reduces on the graphite surface, forming a thin and dense SEI film bottom layer rich in sulfur. FEC or VC further reduces and polymerizes on the DTD-constructed bottom layer, forming a highly cross-linked polycarbonate outer layer. The two work synergistically to construct a bilayer SEI film with both low impedance and high thermal stability, effectively suppressing the continuous reduction and decomposition of the electrolyte at the negative electrode interface at high temperatures.
[0018] Furthermore, the positive electrode interface stabilizer of the electrolyte B includes at least one of lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, and methylene disulfonate, and the mass fraction of the positive electrode interface stabilizer is 0.1wt% to 5wt% of the total mass of the electrolyte B.
[0019] Furthermore, the dehydrating and acid-suppressing additive for electrolyte B includes at least one of tris(trimethylsilyl)phosphate, trimethylsilylimidazolium, trimethylsilylazolidinone, dimethyldiphenoxysilane, N-acetylcaprolactam, and cyclopentyl isocyanate, wherein the mass fraction of the dehydrating and acid-suppressing additive is 0.1wt% to 3wt% of the total mass of electrolyte B. The silicon-oxygen bonds of the dehydrating and acid-suppressing additive tris(trimethylsilyl)phosphate preferentially react with trace amounts of water and HF in the electrolyte to generate inert silane derivatives, thereby reducing the content of free water and HF in the electrolyte, inhibiting the hydrolysis cycle of lithium hexafluorophosphate and the dissolution of positive electrode metal ions, and fundamentally reducing the damage of acid corrosion to the positive and negative electrode interface films.
[0020] Secondly, the present invention provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the electrolyte is the lithium-ion battery composite electrolyte described in any of the above technical solutions.
[0021] Furthermore, the positive electrode active material of the positive electrode sheet is a medium-nickel ternary material, and the molecular formula of the medium-nickel ternary material is LiNi. x Co y Mn 1-x-yO2, where x = 0.65~0.75, y = 0.08~0.20.
[0022] Using medium-nickel ternary materials as the positive electrode active material, in conjunction with the composite electrolyte of this invention, can increase the charging voltage to 4.35~4.5V, with an energy density close to the conventional voltage level of high-nickel materials. At the same time, the risk of metal ion dissolution is significantly lower than that of high-nickel materials, combining the advantages of energy density and safety.
[0023] Thirdly, the present invention provides a method for preparing the lithium-ion battery, the method comprising the following steps: (1) Assemble the positive electrode, negative electrode and separator into an electrode assembly and put it into the battery casing. Perform pre-sealing treatment and leave at least one side as a liquid injection port. (2) Inject electrolyte A, let it stand, and then perform the first formation to form an initial SEI film on the surface of the graphite anode; (3) After the first formation, electrolyte B is injected, and after standing, it is packaged; (4) A second formation is carried out to form a CEI film on the surface of the positive electrode.
[0024] This invention employs a stepwise electrolyte injection and stepwise formation process, in which electrolyte A and electrolyte B are injected in steps and play their roles in different formation stages, thereby separating the formation of the negative electrode SEI film and the positive electrode CEI film in time and space, avoiding mutual interference between the two types of additives, and thus obtaining high-quality negative electrode SEI film and positive electrode CEI film simultaneously.
[0025] Further, the first formation includes: charging to 3.0V~3.65V with a constant current of 0.01C~0.1C; the second formation includes: charging to 4.35V~4.5V with a constant current and constant voltage of 0.1C~1C, and then discharging to 2.8V with a constant current of 0.1C~1C.
[0026] The first formation uses a low current density (0.01C~0.1C) to slowly charge to 3.0~3.65V, which is beneficial for forming a uniform, dense and defect-free initial SEI film on the graphite surface, avoiding the loose or uneven film layer caused by high current film formation. The second formation uses a higher current density to charge to 4.35~4.5V, and with the positive electrode interface stabilizer in electrolyte B, a complete CEI film can be quickly formed on the positive electrode surface.
[0027] Furthermore, the conditions for standing after injecting electrolyte A are: temperature 40~50℃, time 12~36 hours; the conditions for standing after injecting electrolyte B are: temperature 40~50℃, time 12~36 hours.
[0028] Furthermore, in step (3), before injecting electrolyte B, there is also a step of aging and venting the battery after the first formation.
[0029] Furthermore, the aging and venting process includes: placing the battery after the first formation in an environment of 40~50℃ for 6~24 hours for aging, and then venting under vacuum conditions.
[0030] After the first formation, the battery is left to stand at 40-50°C for 6-24 hours to allow the byproduct gases generated during the formation process to be fully released. Then, the gases are completely removed from the battery system through vacuum degassing. This prevents these gases from reacting with the functional components in electrolyte B during the second formation and subsequent use, thereby ensuring the formation quality of the positive electrode CEI film and the long-term storage stability of the battery.
[0031] In existing technologies, the single-injection process needs to take into account the requirements of the positive and negative electrode interfaces, which leads to mutual interference between the negative electrode film-forming additives and the positive electrode interface stabilizers, making it difficult to achieve optimal control of the positive and negative electrode interfaces at the same time. Moreover, conventional secondary injection processes mostly use electrolytes of the same composition, which only serve to supplement the electrolyte and cannot specifically solve the problem of differentiated failure of the positive and negative electrode interfaces under high pressure and high temperature. This invention employs a "stepwise electrolyte injection design with functionally differentiated electrolytes": the first injection uses electrolyte A, containing only negative electrode film-forming additives such as VC / FEC, which preferentially induces the formation of a dense, defect-free initial SEI film on the graphite negative electrode during the first formation stage. Since electrolyte A does not contain positive electrode active additives, it avoids interference with negative electrode film formation, ensuring the integrity of the negative electrode SEI film. After aging and venting, the second injection uses electrolyte B, containing positive electrode interface stabilizers such as LiDFOB / LiPO2F2 and water-removing and acid-suppressing additives. During the second formation stage, it precisely constructs a high-voltage resistant CEI film on the positive electrode. Simultaneously, the functional additives in electrolyte B can inhibit electrolyte decomposition and gas generation during high-temperature storage / cycling, stabilizing the electrolyte composition. Ultimately, this achieves stepwise independent control of the positive and negative electrode interfaces, solving the technical pain point of poor battery cycle stability under high voltage and high temperature.
[0032] The additives in the electrolyte system exhibit a multi-level synergistic film-forming reaction mechanism. Electrolyte A uses a high amount of DTD as the core negative electrode film-forming additive, which can be used alone with VC and FEC, or simultaneously. High DTD content preferentially accumulates at the edge defect sites of the graphite negative electrode and preferentially undergoes reduction reactions to passivate highly active sites, inhibiting the continuous reduction side reactions of the electrolyte solvent; however, the passivation film formed solely by DTD has poor continuity and insufficient mechanical stability. When DTD and VC are used synergistically, DTD passivates highly active sites, and VC is further reduced and decomposed to generate flexible alkyl lithium carbonate organic components, thereby constructing a continuous and resilient SEI organic framework, compensating for the poor film continuity of DTD. When DTD and FEC are used synergistically, DTD pre-passivates the active edges of graphite, and FEC electrochemically reduces and continuously generates the LiF inorganic phase, endowing the SEI film with excellent reduction resistance and solvent penetration resistance. When a ternary compound of DTD, VC, and FEC is used, it can simultaneously possess the advantages of the above two binary systems. The organic and inorganic phases are intertwined, constructing a more dense, stable, and crack-resistant composite SEI film. At the same time, no positive electrode functional additives are introduced into electrolyte A, avoiding competitive reduction of the positive electrode interface stabilizer on the negative electrode surface, ensuring that the synergistic effect of the negative electrode film formation system is not interfered with.
[0033] In electrolyte system B used for secondary injection, LiDFOB and LiPO2F2 are the core components for constructing the positive electrode CEI film, and they exhibit a significant synergistic effect in film formation. While the borate interface film formed by the decomposition of LiDFOB alone possesses good ionic conductivity, its resistance to hydrolysis is relatively weak; the fluorophosphate film formed using only LiPO2F2 lacks toughness and is easily damaged during cycling. When both coexist, a boron-phosphorus composite CEI passivation layer can be co-deposited on the high-voltage positive electrode surface, balancing ionic conductivity and antioxidant stability, effectively preventing direct contact between the electrolyte and the positive electrode active material, and inhibiting transition metal dissolution. However, this boron-phosphorus composite CEI membrane has microscopic pores, making it susceptible to oxidation side reactions as the electrolyte solvent can easily permeate through these pores and contact the positive electrode under high voltage conditions. PS and MMDS are more likely to preferentially oxidize and deposit at these pore defects, blocking interfacial transport channels, inhibiting continuous solvent oxidation, and forming a complementary and synergistic bilayer interfacial passivation structure with the core film-forming components. Furthermore, TMSP can be selectively introduced according to system requirements. TMSP can complex trace amounts of water and HF generated from lithium salt hydrolysis within the system, continuously removing acidic impurities and mitigating CEI membrane hydrolysis aging. By using a step-by-step injection sequence to isolate the two additive systems, cross-reactions caused by the coexistence of the negative electrode film-forming additive and the positive electrode stabilizer are prevented, fully releasing the synergistic effect of each additive group.
[0034] Compared with the prior art, the present invention has the following beneficial effects: (1) Significantly improves the capacity retention and recovery rate after high temperature and high pressure storage, effectively extending the battery's service life under high temperature conditions.
[0035] (2) By using the step-by-step liquid injection process, the negative electrode is injected first to form a film, and the positive electrode is injected second to form a film. This avoids the problem of mutual interference between the positive and negative electrode additives during conventional single liquid injection, so that the positive and negative electrode interface films can be independently optimized to the best state. This achieves precise interface control from the process level, and mass production can be carried out without additional equipment modification.
[0036] (3) All additives in this invention are commercially available and mature varieties. The solution preparation process is simple and compatible with existing battery production lines. Only one additional liquid injection and formation step is required to improve performance. It has extremely high industrial application value and cost-effectiveness. Detailed Implementation
[0037] The technical solutions of this disclosure will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are only some embodiments of this disclosure, not all embodiments, and are only used to illustrate this disclosure, and should not be regarded as limiting the scope of this disclosure. Based on the embodiments in this disclosure, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this disclosure. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0038] The present invention will be described in detail below with reference to specific embodiments.
[0039] The preparation methods of electrolyte A and electrolyte B in the following embodiments are as follows: The preparation method of electrolyte A is as follows: In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed evenly according to the formula. LiPF6 and LiFSI lithium salt are slowly added and stirred at 25±2℃ until the lithium salt is completely dissolved. Then, the corresponding negative electrode film-forming additives (DTD, FEC and / or VC) are added according to the formula, and stirring is continued for 2 hours until completely dissolved to obtain electrolyte A.
[0040] The preparation method of electrolyte B is as follows: In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), propylene carbonate (PC) and ethyl methyl carbonate (EMC) are mixed evenly according to the formula. LiPF6 and LiFSI lithium salts are slowly added and stirred at 25±2℃ until the lithium salts are completely dissolved. Then, 1,3-propanesulfonyl lactone (PS) and / or methylene disulfonate (MMDS), tris(trimethylsilyl) phosphate (TMSP), lithium difluorophosphate (LiPO2F2), lithium difluorooxalate borate (LiODFB) and / or lithium dioxalate borate (LiBOB) are added in sequence according to the formula. After each additive is added, the mixture is stirred for 15-20 minutes. After all additives are added, the mixture is stirred for 2 hours until completely dissolved to obtain electrolyte B.
[0041] Both electrolyte A and electrolyte B were placed at 25±2℃ for 12 hours before injection to ensure that the electrolytes were fully matured and that the components were evenly dispersed.
[0042] Examples 1-16 Preparation of ternary positive electrode sheets With LiNi 0.65 Co 0.15 Mn 0.20 O2 (NCM) was used as the positive electrode active material, and graphite as the negative electrode active material. A lithium-ion battery positive electrode slurry was prepared by uniformly mixing the positive electrode active material, conductive agent EX671D, and binder polyvinylidene fluoride (PVDF) at a mass ratio of 97:2:1. N-methylpyrrolidone (NMP) was used as the solvent, and the amount of NMP added was adjusted to achieve a solid content of 72 wt%. The uniformly mixed slurry was then evenly coated onto a 15 μm thick aluminum foil current collector using a slot extrusion coating method, with the coating surface density controlled at 200-220 g / m². The coated aluminum foil was then placed in a 120℃ hot air drying oven for 12 hours to remove the solvent and cure the slurry. After drying, the electrode sheets are compacted by a roller press to control the compaction density to 3.6-3.8 g / cm³. Finally, the compacted electrode sheets are punched into rectangular electrode sheets with a width of 50 mm and a length of 300 mm by a precision punching equipment to obtain ternary positive electrode sheets with a loading of 10-11 mg / cm². After punching, there are no burrs or powder shedding on the edges of the electrode sheets.
[0043] Preparation of graphite negative electrode sheet A lithium-ion battery anode slurry was prepared by uniformly mixing graphite anode active material, conductive agent Super P (SP), conductive agent single-walled carbon nanotubes (SECNT), binder sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) in a mass ratio of 96:1:0.02:1.25:1.7. The solvent was deionized water, added to achieve a solid content of 52 wt%. During preparation, graphite, SP, and SECNT were first dispersed in deionized water at a high speed of 18 rpm / 2200 rpm for 1 hour to ensure a uniform conductive network. Then, CMC aqueous solution was added and stirred at 18 rpm / 3200 rpm for 2.5 hours. Finally, SBR emulsion was added and stirred at 12 rpm / 1000 rpm for 1 hour to obtain a uniform, stable, and agglomerated anode slurry. The uniformly mixed slurry was coated onto an 8μm thick copper foil current collector using a microgravure coating method, with the coating surface density controlled at 100-110 g / m². After coating, it was placed in an 80℃ hot air drying oven for 16 hours to completely remove moisture. The dried negative electrode sheet was compacted by a roller press, with the compaction density controlled at 1.5-1.6 g / cm³. Subsequently, it was punched into rectangular electrode sheets with a width of 52mm and a length of 310mm (slightly larger than the positive electrode sheet to ensure coverage), resulting in a graphite negative electrode sheet with a loading of 5-5.5 mg / cm². The electrode sheet surface was smooth and had good adhesion.
[0044] Fabrication of pouch lithium-ion batteries (dual electrolyte dual formation process) Electrode assembly and pre-packaging: The ternary positive electrode sheet, graphite negative electrode sheet, and 12μm thick polypropylene / polyethylene / polypropylene (PP / PE / PP) composite separator prepared above are assembled into an electrode assembly. The assembly method adopts a stacking process, starting with the negative electrode sheet and stacking in the order of "negative electrode-separator-positive electrode-separator", ending with the negative electrode sheet, for a total of 31 layers (15 layers of positive electrode and 16 layers of negative electrode). This ensures that the separator completely covers the edge of the positive electrode sheet and avoids direct contact between the positive and negative electrodes. After the stacking is completed, the tabs are welded. The positive tab is ultrasonically welded to the current collector of the positive electrode sheet using an aluminum strip with a thickness of 0.1-0.2mm and a width of 3-5mm. The negative tab is ultrasonically welded to the current collector of the negative electrode sheet using a nickel strip. The electrodes with welded tabs are then assembled into an aluminum-plastic composite film packaging shell. The aluminum-plastic film is pre-sealed on one side (only three sides are sealed, leaving one side as an injection port).
[0045] First electrolyte injection and formation (electrolyte A): Electrolyte A was injected through the pre-reserved injection port, with a total injection volume of 30g. Electrolyte A was injected according to the injection ratio. After injection, the battery was allowed to stand at 45℃ for 24 hours to ensure that the electrolyte fully wetted the electrode assembly and separator and formed a preliminary SEI film. The first formation process was then performed, with the following steps: charging at a constant current of 0.03C to 3.0V (a critical stage for SEI film formation), standing for 5 minutes, then charging at a constant current of 0.08C to 3.65V, and standing for 5 minutes to complete the initial film formation activation. During the first formation process, the battery was placed in a constant temperature environment of 25±2℃.
[0046] Aging and venting: After the first formation is completed, the battery is placed in an environment of 45℃ and left to stand for 24 hours for aging treatment. After aging, the battery is evacuated and vented under a vacuum of ≤-0.09MPa for 30-60 seconds to remove the gas generated during the formation process.
[0047] Second injection (electrolyte B): After venting, inject electrolyte B through the reserved injection port. The total injection volume of electrolyte is 30g. Electrolyte B is injected according to the injection ratio. After injection, let stand at 45℃ for 24 hours to ensure that the two electrolytes are fully mixed and that the mixed electrolyte completely wets the electrode and the diaphragm to form a stable ion transport channel.
[0048] Final encapsulation and second formation: After settling, the injection port is vacuum-sealed under the following conditions: vacuum degree ≤ -0.09MPa, sealing temperature 180-200℃, sealing pressure 0.3-0.5MPa, sealing time 3-5 seconds. During encapsulation, all internal gases are completely eliminated to ensure a tight seal. A second formation process is then performed: charging at 0.33C constant current and constant voltage to 4.4V, with a cutoff current of 0.05C, settling for 5 minutes, and then discharging at 0.33C constant current to 2.8V to optimize the electrode interface and activate battery performance. During the second formation process, the battery is kept in a constant temperature environment of 25±2℃.
[0049] Post-processing steps: After the second formation, the batteries are aged in a 45°C environment for 48 hours. Then, capacity sorting (capacity deviation ≤3%), self-discharge testing (7-day self-discharge rate ≤2%), high-temperature storage testing and other processes are carried out.
[0050] Specific formulations of Examples 1-16 The specific formulations of electrolyte A and electrolyte B in Examples 1-16 are shown in Table 1. The mass ratio of electrolyte A to electrolyte B, as well as the specific composition of electrolyte A and electrolyte B, are listed in Table 1. In each example, the total mass of electrolyte A and the total mass of electrolyte B are 100 parts. After preparing electrolyte A and electrolyte B according to the mass ratio shown in Table 1, they are then mixed according to the A / B mass ratio in Table 1.
[0051] Table 1: Formulations of Electrolyte A and Electrolyte B for Examples 1-16
[0052] The full names of the compounds corresponding to the abbreviations in Table 1 are as follows: LiPF6 is lithium hexafluorophosphate, LiFSI is lithium difluorosulfonyl imide, EC is ethylene carbonate, EMC is methyl ethyl carbonate, PC is propylene carbonate, DTD is ethylene sulfate, FEC is fluoroethylene carbonate, VC is vinylene carbonate, PS is 1,3-propane sulpholactone, MMDS is methane disulfonate methylene, TMSP is tris(trimethylsilyl)phosphate, LiPO2F2 is lithium difluorophosphate, LiODFB is lithium difluorooxalate borate, and LiBOB is lithium dioxalate borate.
[0053] Battery preparation methods of Comparative Examples 1-12 Comparative Examples 1-12 used the same ternary positive electrode, graphite negative electrode, separator, and battery assembly process as the Examples, with the only difference being the electrolyte formulation and the electrolyte injection formation process.
[0054] Comparative Examples 1-8 and Comparative Example 12 adopted a single-injection, single-formation process. The specific steps are as follows: Electrolyte injection: Inject 30g of electrolyte through the pre-reserved injection port; after injection, let stand at 45°C for 24 hours to ensure that the electrolyte fully wets the electrode assembly and diaphragm.
[0055] Formation: After standing, the injection port is vacuum sealed under the same conditions as in the example. Then, a formation process is performed. The formation process is as follows: charge to 3.0V with a constant current of 0.03C, stand for 5 minutes, charge to 3.65V with a constant current of 0.05C, stand for 5 minutes; charge to 4.4V with a constant current and constant voltage of 0.33C (cutoff current 0.05C), stand for 5 minutes, and finally discharge to 2.8V with a constant current of 0.33C to complete the formation and activation.
[0056] In Comparative Examples 9-11, the amount of electrolyte A injected was 22.5g and the amount of electrolyte B injected was 7.5g. Comparative Examples 9-11 adopted stepwise injection and two formation processes, and the formation process was consistent with the steps of the examples.
[0057] Post-processing: After formation, the battery is aged in a 45°C environment for 48 hours, followed by capacity sorting (capacity deviation ≤3%), self-discharge test (7-day self-discharge rate ≤2%), high-temperature storage test and other processes.
[0058] The electrolyte formulations for Comparative Examples 1-12 are shown in Table 2, with a total electrolyte mass of 100 parts in each comparative example.
[0059] Table 2: Electrolyte formulations for Comparative Examples 1-12
[0060] Performance testing High-temperature storage performance test The ternary graphite lithium-ion batteries prepared in Examples 1-16 and Comparative Examples 1-12 were subjected to high-temperature storage performance tests. The test methods are as follows: After formation and aging, the batteries were charged at 0.33C constant current and constant voltage to 4.4V (cutoff current 0.05C) at 25±2℃. After resting for 5 minutes, they were discharged at 0.33C constant current to 2.8V, and the discharge capacity was recorded as the initial capacity. Subsequently, the batteries were charged at 0.33C constant current and constant voltage to 4.4V (cutoff current 0.05C), and the fully charged batteries were placed in a constant temperature drying oven at 60±2℃ for 30 days. After the drying period, the batteries were removed and cooled at 25±2℃ for 4 hours, and then discharged at 0.33C constant current to 2.8V at 25±2℃. The discharge capacity was recorded as the post-drying capacity, and the capacity retention rate was calculated (= post-drying capacity / initial capacity × 100%). The battery was then charged to 4.4V at a constant current and constant voltage of 0.33C in an environment of 25±2℃ (cutoff current 0.05C), and discharged to 2.8V at a constant current of 0.33C after resting for 5 minutes. This cycle was repeated 3 times. The discharge capacity in the third week was recorded as the recovered capacity, and the capacity recovery rate was calculated (=recovered capacity / initial capacity×100%).
[0061] The test results are shown in Table 3.
[0062] Table 3: Capacity retention and recovery rate of ternary graphite lithium-ion batteries from Examples 1-16 and Comparative Examples 1-12 after being stored at 60°C for 30 days.
[0063] Based on the performance test data, it can be seen that in Example 1 16. By fully employing the solvent differentiation substitution, additive compounding optimization, and step-by-step liquid injection formation process of this invention, the battery retains a capacity of 90.8% after being stored at 60°C for 30 days. 93.0%, with a capacity recovery rate of up to 95.9%. 98.0%; In each of the comparative examples 1-12, the performance significantly decreased, with capacity retention of only 86.0%, due to the absence of one or more of the following: solvent differentiation, additive formulation, or step-by-step process. 88.6%, capacity recovery rate 91.0% 93.8%.
[0064] Solvent Differentiation Substitution Verification: The lithium salt system, additive system, and step-by-step electrolyte injection process were all kept consistent between Comparative Example 5 and Comparative Example 9; the difference was that electrolyte B in Comparative Example 9 did not contain PC solvent. Example 5 showed a capacity retention rate of 92.2% and a recovery rate of 97.2%, significantly higher than Comparative Example 9 (88.3%, 93.2%). This confirms that the differentiated solvent design of electrolyte A (EC / EMC) and electrolyte B (PC / EMC) is a key technical feature. PC possesses low melting point and high boiling point characteristics, and its weak solvation effect can suppress the dissolution and damage of the positive electrode CEI film under high-temperature conditions. The different roles of PC and EC solvents are adapted to the differentiated requirements of negative electrode film formation and positive electrode high-voltage withstand. If electrolytes A and B use the same solvent system, excellent high-temperature shelf-life performance cannot be obtained.
[0065] Additive formulation optimization verification: Comparative Example 5 with Comparative Examples 10 and 11: All examples employed a step-by-step electrolyte injection process and differentiated solvent systems for electrolytes A and B. In Comparative Example 10, removing the LiPO2F2 / LiODFB positive electrode interface stabilizer from electrolyte B reduced the capacity retention to 88.6%; in Comparative Example 11, removing the water-removing and acid-suppressing additive TMSP from electrolyte B reduced the capacity retention to 88.1%. On the negative electrode side, a dense SEI passivation film was constructed using a combination of DTD and VC / FEC; on the positive electrode side, LiPO2F2 and boron-based lithium salts were co-deposited to form boron. Phosphorus-based composite CEI membranes utilize PS / MMDS to seal CEI interface pores and TMSP to capture trace water and HF impurities within the system. Only a complete combination of negative electrode film-forming additives, positive electrode interface stabilizers, and water-removing and acid-suppressing additives can achieve synergistic protection of the positive and negative electrode interfaces. The absence of any one of these functional components significantly degrades high-temperature storage performance.
[0066] Stepwise liquid injection formation process verification: Comparative Example 5 with Comparative Examples 8 and 12: The three groups of lithium salts, solvents, and all additive components were completely identical. Comparative Example 8 was a conventional single liquid injection; Comparative Example 12 was a single liquid injection after mixing all components. Example 5 achieved a capacity retention of 92.2%, significantly better than Comparative Example 8 (87.9%) and Comparative Example 12 (87.2%). The results indicate that even with all the required components, after eliminating the stepwise liquid injection sequence isolation, the positive electrode functional additives will be competitively reduced and consumed on the negative electrode surface, causing mutual interference between the positive and negative electrode film formation processes. The stepwise liquid injection process enables the sequential stepwise construction of the negative electrode SEI and positive electrode CEI, while simultaneously allowing for the secondary introduction of PC solvent, which is a necessary process condition to fully leverage the synergistic effect of solvents and additives.
[0067] Comparing Example 5 and Example 13, with the same formulation, only the mass ratio of electrolyte A / B was adjusted from 3:1 to 2:1, and the proportion of electrolyte B was moderately increased, the battery performance was further improved, further demonstrating the benefit of differentiated electrolyte step-by-step supply to interface optimization.
[0068] The above comparative results demonstrate that the high-pressure and high-temperature shelf performance of the present invention is achieved through the synergistic effect of solvent differentiation and substitution, additive compound optimization, and step-by-step liquefaction formation process; the technical effect of the present invention cannot be achieved by relying solely on single solvent improvement, additive compounding, or process adjustment.
[0069] The technical solution of this invention is reasonably designed and highly practical. It only requires adding one liquid injection and formation process to the existing production line, without the need for major modifications to the existing battery production equipment. It is easy to achieve industrial mass production. It not only provides key technical support for the high-voltage and high-temperature application of medium-nickel ternary graphite batteries, but also has great significance for promoting the technological upgrading of the power battery and energy storage battery industry.
[0070] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A composite electrolyte for lithium-ion batteries, characterized in that, The composite electrolyte includes electrolyte A and electrolyte B; The electrolyte A includes lithium salt, ester solvent and negative electrode film-forming additive; The electrolyte B includes lithium salt, ester solvent, positive electrode interface stabilizer, negative electrode film-forming additive, and dehydration and acid-suppressing additive. Electrolyte A accounts for 50wt% to 80wt% of the total mass of the composite electrolyte, and electrolyte B accounts for 20wt% to 50wt% of the total mass of the composite electrolyte.
2. The lithium-ion battery composite electrolyte according to claim 1, characterized in that, The lithium salts in electrolyte A and electrolyte B each independently include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bisfluorosulfonylimide, lithium bistrifluoromethanesulfonylimide, lithium difluorooxalate borate, lithium bisoxalate borate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium fluorosulfonate, and lithium perchlorate.
3. The lithium-ion battery composite electrolyte according to claim 2, characterized in that, The lithium salts in electrolyte A and electrolyte B are mixtures of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, with the mass ratio of lithium hexafluorophosphate to lithium bis(fluorosulfonyl)imide in electrolyte A and electrolyte B being 12:1 to 1:4 independently, respectively. Based on the total mass of electrolyte A, the mass fraction of lithium salts in electrolyte A is 10% to 25%, and based on the total mass of electrolyte B, the mass fraction of lithium salts in electrolyte B is 10% to 25%.
4. The lithium-ion battery composite electrolyte according to claim 1, characterized in that, The ester solvents in electrolyte A and electrolyte B each independently include at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, and methyl butyrate.
5. The lithium-ion battery composite electrolyte according to claim 4, characterized in that, The ester solvent of electrolyte A is a mixture of ethylene carbonate and methyl ethyl carbonate, wherein the volume ratio of ethylene carbonate to methyl ethyl carbonate is 1:4 to 4:1; the ester solvent of electrolyte B is a mixture of propylene carbonate and methyl ethyl carbonate, wherein the volume ratio of propylene carbonate to methyl ethyl carbonate is 1:9 to 1:
1.
6. The lithium-ion battery composite electrolyte according to claim 5, characterized in that, The volume ratio of ethylene carbonate to methyl ethyl carbonate in electrolyte A is 3:7; the volume ratio of propylene carbonate to methyl ethyl carbonate in electrolyte B is 3:
7.
7. The lithium-ion battery composite electrolyte according to claim 1 or 2, characterized in that, The negative electrode film-forming additive of electrolyte A includes at least one of vinylene carbonate, fluoroethylene carbonate, and vinyl sulfate, and the mass fraction of the negative electrode film-forming additive of electrolyte A is 0.1wt% to 5wt% of the total mass of electrolyte A; the negative electrode film-forming additive of electrolyte B includes at least one of vinylene carbonate and 1,3-propane sulpholactone, and the mass fraction of the negative electrode film-forming additive of electrolyte B is 0.1wt% to 3wt% of the total mass of electrolyte B.
8. The lithium-ion battery composite electrolyte according to claim 7, characterized in that, The negative electrode film-forming additive of electrolyte A is a mixture of vinyl sulfate and fluorovinyl carbonate, or a mixture of vinyl sulfate and vinylene carbonate, or a mixture of vinyl sulfate, fluorovinyl carbonate and vinylene carbonate.
9. The lithium-ion battery composite electrolyte according to claim 1, characterized in that, The positive electrode interface stabilizer of the electrolyte B includes at least one of lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, and methylene disulfonate, and the mass fraction of the positive electrode interface stabilizer is 0.1wt% to 5wt% of the total mass of the electrolyte B.
10. The lithium-ion battery composite electrolyte according to claim 1, characterized in that, The dehydration and acid-suppressing additive of electrolyte B includes at least one of tris(trimethylsilyl)phosphate, trimethylsilylimidazolium, trimethylsilylazolidinone, dimethyldiphenoxysilane, N-acetylcaprolactam, and cyclopentyl isocyanate, and the mass fraction of the dehydration and acid-suppressing additive is 0.1wt% to 3wt% of the total mass of electrolyte B.
11. A lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that, The electrolyte is the lithium-ion battery composite electrolyte according to any one of claims 1 to 10.
12. The lithium-ion battery according to claim 11, characterized in that, The positive electrode active material of the positive electrode sheet is a medium-nickel ternary material, and the molecular formula of the medium-nickel ternary material is LiNi. x Co y Mn 1-x-y O2, where x = 0.65~0.75, y = 0.08~0.
20.
13. A method for preparing a lithium-ion battery as described in claim 11 or 12, characterized in that, Includes the following steps: (1) Assemble the positive electrode, negative electrode and separator into an electrode assembly and put it into the battery casing. Perform pre-sealing treatment and leave at least one side as a liquid injection port. (2) Inject electrolyte A, let it stand, and then perform the first formation to form an initial SEI film on the surface of the graphite anode; (3) After the first formation, electrolyte B is injected, and after standing, it is packaged; (4) A second formation is carried out to form a CEI film on the surface of the positive electrode.
14. The preparation method according to claim 13, characterized in that, The first formation includes: charging to 3.0V~3.65V with a constant current of 0.01C~0.1C; the second formation includes: charging to 4.35V~4.5V with a constant current and constant voltage of 0.1C~1C, and then discharging to 2.8V with a constant current of 0.1C~1C.
15. The preparation method according to claim 13, characterized in that, The conditions for allowing the electrolyte A to stand after injection are: temperature 40~50℃, time 12~36 hours; the conditions for allowing the electrolyte B to stand after injection are: temperature 40~50℃, time 12~36 hours.
16. The preparation method according to claim 13, characterized in that, In step (3), before injecting electrolyte B, there is also a step of aging and venting the battery after the first formation.
17. The preparation method according to claim 16, characterized in that, The aging and venting process includes: placing the battery after the first formation in an environment of 40~50℃ for 6~24 hours for aging, and then venting under vacuum conditions.
